Application of Combine Clapping and Vibrating to Improve Airway Clearance in Children with Acute Respiratory Tract Infections (ISPA) - Novia Nurliana; Rini Palupi, Rini Palupi; Anggi Kusuma (Jurnal Kesehatan Cendikia Jenius, 2025)
Acute respiratory tract infections (ARIs) remain a global health issue, with the prevalence of ARIs in Indonesia reaching 1,017,290 million cases, and the highest prevalence occurring in children aged 5-14 years (182,338 cases). ARIs often lead to increased mucus production in children's lungs. One effective nursing intervention to help expel sputum is the application of the combine clapping and vibrating technique for patients with ineffective airway clearance. This study aims to assess the effectiveness of this technique at Puskesmas Punggur, Kota Metro, from July 18-20, 2024. This is a descriptive study using a case study approach. Data was collected through interviews and observations. The results of the study show that applying the combine clapping and vibrating technique for 3 days, with a duration of 10-15 minutes in the morning and evening, can improve effective coughing, reduce sputum, eliminate additional breathing sounds, alleviate shortness of breath, and normalize respiratory rate. In conclusion, this technique has been proven effective as a non-pharmacological nursing intervention, and its application is recommended for children with respiratory disorders.